Otolith growth rings pattern of Mystus nigriceps from the Tarai River, Kampar Regency, Riau Province - Novita Sari Simandalahi; Deni Efizon; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMystus nigriceps commonly inhabit the Tarai River that is polluted by tofu industrial liquid waste. Low water quality may affects fish growth and that is reflected in the growth ring pattern of the otolith. A research aims to understand the pattern of otolith growth rings in the M. nigriceps was conducted in April to May 2019. The fish was captured  using a cast net, and a scoop net. There were  90 fishes captured (31 males and 59 females). The otolith were removed and shaved. The dark growth ring pattern was investigated using a binocular microscope. Results shown that the standard length of the fish ranged from    75.11 to 150.44 mm and their body weight was 3.27 to 44.82 g. The otolith length was 1.375 to 2.625 mm and its width was ranged from 0.85 to 1.375 mm. Among the fish captured, 82 of them having 1-3 dark rings, indicate that the in certain period the growth of fish in the Tarai River is hampered. The distance between the nucleus and the first dark ring was 0.25 to 0.625 mm and there was no special pattern in the formation of the first dark ring. This fact indicate that the first dark rings are formed individually and it is not formed by periodic events in fish life. The water quality parameter value are as follows, temperature 27-280C; pH 6;  DO 3.2-3.5 mg/L; and CO2 23.09-24.98 mg/L) and it is able to support the life of fish. Keywords: dark ring, growth ring pattern, sagita, catfish, polluted river